Polylactic acid resin foam sheet, sheet molding, and method for manufacturing sheet molding
Patent Information
- Application Number
- JP2023140524
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0012】 本発明よれば、耐熱性に優れたシート成形体を得るための成形工程に要する時間を短縮させることを可能とするポリ乳酸樹脂発泡シートが提供され、耐熱性に優れたシート成形体が提供され、該シート成形体を得るための、ポリ乳酸樹脂発泡シートの成形工程に要する時間を短縮させたシート成形体の製造方法が提供される。
Smart Images

Figure 2025034248000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polylactic acid resin foamed sheet, a sheet molded article, and a method for producing the sheet molded article. [Background technology]
[0002] In recent years, there has been a demand for measures to address the problem of landscape damage caused by illegally dumped packaging materials in places such as mountains, fields, rivers, and coastlines. In light of this, the production of molded articles using polylactic acid resin that can be biodegraded in the natural environment has been considered, and the use of polylactic acid resin foam sheets in various applications has been considered. Conventionally, polylactic acid resin foam sheets have been produced by melt-kneading a foaming agent and a polylactic acid resin composition in an extruder, and then extruding the mixture through a circular die attached to the tip of the extruder.
[0003] This type of polylactic acid resin sheet is used as a base sheet for producing sheet bodies by thermoforming such as match mold forming and vacuum / pressure forming, and is also widely used as a constituent material for formed bodies such as food trays and cups. In producing this type of molded product, a molding die is used to give the original sheet a product shape, and therefore this type of molded product is called a sheet molded product or the like.
[0004] Conventionally, this type of sheet molded body has been produced by carrying out a preheating step in which a polylactic acid resin foam sheet is heated and softened, and then a molding step in which the sheet is shaped to fit the molding surface of a mold after the preheating step. The sheet molding is produced by further carrying out a demolding process in which the polylactic acid resin foam sheet to which the product shape has been imparted after the molding process is removed from the mold, and a trimming process in which the outer periphery of the polylactic acid resin foam sheet removed from the mold is cut to remove excess parts other than the product.
[0005] Generally, a polylactic acid resin foam sheet exhibits higher heat resistance when the polylactic acid resin contained therein has crystallinity and is sufficiently crystallized. However, since polylactic acid resin generally crystallizes slower than polyolefin resins such as polyethylene and polypropylene among crystalline resins, polylactic acid resin foam sheets are usually hardly crystallized during their production. On the other hand, when a polylactic acid resin foam sheet that has been sufficiently crystallized in advance is applied to a molding process, a sheet molding with excellent heat resistance is produced, but the sheet molding may not be able to conform sufficiently to the molding die during thermoforming, making it difficult for the sheet molding to assume the desired shape from the beginning. Therefore, it has been attempted to give heat resistance to a sheet molded body by shaping and crystallizing a polylactic acid resin foam sheet that is not yet crystallized using heated male and female molds as molding dies. Such a heat treatment process for crystallization is called "heat setting" or the like, and in a conventional method for producing a sheet molded body, the heat setting is carried out by shaping a polylactic acid resin foam sheet using a heated molding die and heating the polylactic acid resin foam sheet after shaping for a dozen to several tens of seconds using a molding die heated to about 110°C to sufficiently crystallize the polylactic acid resin (see Patent Document 1 below, paragraph 0074, etc.). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-145058 A Summary of the Invention [Problem to be solved by the invention]
[0007] In a manufacturing method of a sheet molded product using a polystyrene resin foam sheet, such as polystyrene paper (PSP), a mold is used to shape the polystyrene resin foam sheet heated in a preheating step and simultaneously cool the polystyrene resin foam sheet, and the molding step is completed in about a few seconds. On the other hand, in a manufacturing method of a sheet molded product using a polylactic acid resin foam sheet, the molding step takes a long time due to crystallization as described above. Therefore, the present invention has an objective of providing a polylactic acid resin foam sheet that makes it possible to shorten the time required for the molding process to obtain a sheet molded body with excellent heat resistance, and to provide a sheet molded body with excellent heat resistance, and to provide a method for manufacturing a sheet molded body that makes it possible to shorten the time required for the molding process of the polylactic acid resin foam sheet to obtain the sheet molded body. [Means for solving the problem]
[0008] As a result of extensive research conducted by the present inventors in order to solve the above problems, they have found that in the case of a polylactic acid resin foam sheet in which crystallization progresses (the crystallization rate is fast) during the pre-heating step in thermoforming, crystallization progresses to a certain extent before the polylactic acid resin foam sheet is shaped in a mold, thereby shortening the time required for the molding step of the polylactic acid resin foam sheet and producing a sheet molded product with excellent heat resistance.
[0009] That is, in order to solve the above problems, the present invention provides A polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The temperature at which the relative crystallinity reaches 50% (T h ) is 115°C or less.
[0010] In order to solve the above problems, the present invention provides: The present invention provides a thermoformed product of the polylactic acid resin foam sheet, the sheet having a crystallinity of 20% or more.
[0011] In order to solve the above problems, the present invention provides: A method for producing a sheet molded body by thermoforming a resin foam sheet, comprising the steps of: The resin foam sheet is a polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The polylactic acid resin foam sheet is A polylactic acid resin foam sheet having a temperature of 115°C or less when a relative crystallinity of 50% is reached in a cold crystallization peak observed during a temperature rise process at a heating rate of 50°C / min in a heat flux differential scanning calorimetry, a first step of heating the polylactic acid resin foam sheet; The present invention also provides a method for producing a sheet molded body, which comprises a second step of sandwiching the polylactic acid resin foamed sheet subjected to the first step between a mold and producing a sheet molded body. Effect of the Invention
[0012] According to the present invention, a polylactic acid resin foam sheet is provided that makes it possible to shorten the time required for the molding process to obtain a sheet molded body with excellent heat resistance, a sheet molded body with excellent heat resistance is provided, and a method for producing a sheet molded body is provided that shortens the time required for the molding process of the polylactic acid resin foam sheet to obtain the sheet molded body. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing an example of a sheet manufacturing apparatus for producing a polylactic acid resin foam sheet. [Diagram 2] FIG. 2 shows DSC curves obtained by heat flux differential scanning calorimetry of the polylactic acid resin foam sheets used in Examples 1 to 4 at a heating rate of 5° C. / min. [Diagram 3] FIG. 3 shows DSC curves obtained by heat flux differential scanning calorimetry of the polylactic acid resin foam sheets used in Examples 1 to 4 at a heating rate of 50° C. / min. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the present invention will be described below. The polylactic acid resin foam sheet of this embodiment is composed of a polylactic acid resin composition containing polylactic acid resin. In the following, an embodiment of the present invention will be described taking as an example a case where the polylactic acid resin foam sheet is an extrusion foam sheet obtained by an apparatus as shown in FIG. 1. The polylactic acid resin foam sheet of this embodiment can be suitably used to produce a sheet molded product by thermoforming. Examples of such thermoforming include vacuum forming, pressure forming, vacuum-pressure forming, match mold forming, and press forming.
[0015] The polylactic acid resin foam sheet of this embodiment may be, for example, an extruded foam sheet produced by a sheet manufacturing apparatus 100 illustrated in Fig. 1. The sheet manufacturing apparatus 100 illustrated in Fig. 1 includes a tandem extruder 10 and a circular die CD that extrudes the polylactic acid resin composition melt-kneaded in the tandem extruder 10 into a cylindrical shape. The manufacturing apparatus further includes a cooling device CL that air-cools the polylactic acid resin foam sheet extruded into a cylindrical shape from the circular die CD, and a mandrel MD that expands the cylindrical polylactic acid resin foam sheet into a cylindrical shape of a predetermined size.
[0016] The sheet manufacturing apparatus 100 is equipped with a slitting device that cuts open the polylactic acid resin foam sheet after it has passed through the mandrel MD and become a cylindrical shape having a predetermined diameter, and divides it into two strip-shaped sheets, and a winding roller 22 that winds up the polylactic acid resin foam sheet 1 cut and divided by the slitting device after it has passed through multiple rollers 21.
[0017] The extruder upstream of the tandem extruder 10 (hereinafter also referred to as the "first extruder 10a") is provided with a hopper 11 for feeding a polylactic acid resin composition (hereinafter also simply referred to as the "resin composition"), which is the raw material for the polylactic acid resin foam sheet, and a gas inlet 12 for supplying a foaming agent such as a hydrocarbon into the cylinder.
[0018] The sheet manufacturing apparatus 100 of this embodiment is also provided with an extruder (hereinafter also referred to as "second extruder 10b") downstream of the first extruder 10a. In the second extruder 10b, melt-kneading of a resin composition containing a foaming agent is performed. The polylactic acid resin contained in the polylactic acid resin foam sheet has crystallinity. The polylactic acid resin is preferably modified by crosslinking or the like so as to exhibit excellent foaming properties. The modified polylactic acid resin (hereinafter also referred to as "modified polylactic acid resin") may be incorporated into the polylactic acid resin foam sheet by supplying a pre-modified polylactic acid resin to the hopper 11, or may be incorporated into the polylactic acid resin foam sheet by modifying an unmodified polylactic acid resin in the extruder used for producing the polylactic acid resin foam sheet.
[0019] The polylactic acid resin foam sheet of this embodiment is produced so that the crystallinity of the polylactic acid resin contained therein is not excessively increased by the cooling device CL or the mandrel MD during production. Specifically, the polylactic acid resin foam sheet of this embodiment is produced so that the crystallinity is 30% or less. The lower the crystallinity of the polylactic acid resin foam sheet, the better the moldability when producing a sheet molded body. Therefore, the crystallinity of the polylactic acid resin foam sheet may be 27% or less, or may be 25% or less. By having a crystallinity of 30% or less, excessive stretching in the mold during thermoforming is suppressed, and it is possible to suppress the occurrence of shrinkage over time in the obtained sheet molded body.
[0020] On the other hand, it is advantageous for the polylactic acid resin foam sheet to have a certain degree of crystallinity or more in terms of shortening the time required for the molding process and allowing the sheet molded product to exhibit excellent heat resistance. The crystallinity of the polylactic acid resin foam sheet may be 10% or more, or 12% or more.
[0021] The polylactic acid resin foam sheet is preferably formed so as to exhibit a higher degree of crystallinity than the polylactic acid resin foam sheet by a preheating process or the like. The polylactic acid resin foam sheet is preferably formed so as to increase the degree of crystallinity by 5% or more, and preferably so as to increase the degree of crystallinity by 10% or more. The degree of crystallinity that the polylactic acid resin foam sheet can achieve is preferably 25% or more, and more preferably 27% or more. The degree of crystallinity that the polylactic acid resin foam sheet can achieve is usually 60% or less. The degree of crystallinity that the polylactic acid resin foam sheet can achieve may be 55% or less.
[0022] <Melting point, crystallinity> The melting point and crystallinity of the polylactic acid resin foam sheet and the sheet molding can be measured by the methods described in JIS K7121:1987, 2012 and JIS K7122:1987, 2012. The sampling method and heating rate conditions are as follows. The polylactic acid resin foam sheet and the sample cut out from the sheet molded body are filled into the bottom of an aluminum measurement container with 5.5±0.5 mg of the sample without any gaps, and then the aluminum lid is placed on the container. Then, differential scanning calorimetry is performed using a Hitachi High-Tech Science Corporation "NEXTA DSC600" differential scanning calorimeter. A DSC curve can be obtained by heating and cooling the sample in the following steps 1 to 3 under a nitrogen gas flow rate of 20 mL / min. (Step 1) Heat from 30°C to 210°C at a heating rate of 5°C / min (first heating process) and hold for 10 minutes. (Step 2) The sample is quickly removed from the measurement device and allowed to stand for 10 minutes in an environment of 25±10°C, and then returned to the measurement device at 30°C. (Step 3) The temperature is increased from 30°C to 210°C at a heating rate of 5°C / min (second heating process). Alumina is used as the reference material. The melting point was determined using the analysis software attached to the apparatus, and was determined to be the top temperature of the melting peak observed during the second heating process as shown in Figure 2. The endothermic heat amount (a1) and the heat generation amount (b1) can be calculated using analysis software attached to the device. Specifically, as shown in FIG. 2, the endothermic heat amount (a1) can be calculated from the area enclosed by the DSC curve and a straight line connecting the point where the DSC curve leaves the low-temperature baseline in the first heating process and the point where the DSC curve returns to the high-temperature baseline. The heat generation amount (b1) can be calculated from the area enclosed by the DSC curve and a straight line connecting the point where the DSC curve leaves the low-temperature baseline in the first heating process and the point where the DSC curve returns to the high-temperature baseline. The degree of crystallinity can be calculated from the endothermic amount (a1) and the exothermic amount (b1) according to the following formula (1). Degree of crystallinity (%) = {(absolute value of endothermic heat (a1) (J / g) - absolute value of exothermic heat (b1) (J / g)) ÷ heat of fusion of perfect crystals (J / g)} × 100 (1) The heat of fusion of a perfect crystal represents the amount of heat when 100% crystallization occurs. Note that the heat of fusion of a perfect crystal in the above formula (1) is 93 J / g, which is the heat of fusion of a perfect crystal of polylactic acid resin.
[0023] In the pre-heating step in thermoforming, the sheet is heated to a predetermined temperature in a short time (the heating rate is fast). If the polylactic acid resin foam sheet is one in which crystallization proceeds even under such fast heating rate conditions (the crystallization rate is fast), the heat setting time can be shortened, and in some cases, even if the heat setting step itself is eliminated, it becomes easy to produce a sheet molded product with excellent heat resistance. The polylactic acid resin foam sheet in this embodiment has a temperature (T h The temperature at which the relative crystallinity is 50% (T h The lower the temperature at which the relative crystallinity is 50% (T h ) is preferably 110° C. or less. In addition, the temperature at which the relative crystallinity becomes 50% (T h ) may be 85°C or higher, or 95°C or higher.
[0024] The polylactic acid resin foam sheet has a crystallization onset temperature (T s The crystallization onset temperature (T s ) may be 60°C or higher, or 70°C or higher.
[0025] The polylactic acid resin foam sheet has a crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h The difference (ΔT) between the crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h The smaller the difference (ΔT) between the crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h ) may be 33° C. or less, or may be 30° C. or less. This temperature difference may be, for example, 15° C. or more, or 20° C. or more.
[0026] In order to allow the polylactic acid resin foam sheet to exhibit the above-mentioned properties, it is preferable to suppress the excessive crystallization in the step of producing the polylactic acid resin foam sheet. In the above-mentioned extruded foam sheet, the cylindrical foam sheet extruded from the extruder is quickly cooled to a temperature lower than the temperature range in which the polylactic acid resin crystallizes, thereby obtaining a polylactic acid resin foam sheet containing a large amount of crystallizable components. Specifically, the air-cooling temperature immediately after extrusion and the set temperature of the mandrel are set lower than those of general manufacturing conditions, or the air volume during air-cooling and the amount of refrigerant circulating in the mandrel are increased, thereby obtaining a polylactic acid resin foam sheet containing a large amount of crystallizable components. In addition, in order to allow the polylactic acid resin foam sheet to exhibit the above-mentioned properties, it is preferable to use a resin composition having a high proportion of crystallizable components, as described below.
[0027] The polylactic acid resin foam sheet preferably has an endothermic heat (a2) of 25 J / g or more observed during a temperature rise process at a heating rate of 50° C. / min in heat flux differential scanning calorimetry. The endothermic heat (a2) may be, for example, 30 J / g or more, or 35 J / g or more. The endothermic heat (a2) may be, for example, 60 J / g or less.
[0028] The polylactic acid resin foam sheet has a calorific value (b2) of 25 J / g or more observed during a temperature rise process at a heating rate of 50° C. / min in heat flux differential scanning calorimetry. The calorific value (b2) may be 26 J / g or more, or 27 J / g or more. The calorific value (b2) is preferably 31 J / g or less.
[0029] The crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h ) can be determined by the method described in the Examples.
[0030] The resin composition contains a crystalline polylactic acid resin as a main component. The polylactic acid resin refers to a polymer containing 50 mol % or more of lactic acid component units. The polymer is, for example, (1) Polymers of lactic acid only, (2) Copolymers of lactic acid and other aliphatic hydroxycarboxylic acids, (3) Copolymers of lactic acid, aliphatic polyhydric alcohols, and aliphatic polycarboxylic acids, (4) Copolymers of lactic acid and aliphatic polycarboxylic acids, (5) Copolymers of lactic acid and aliphatic polyhydric alcohols, (6) A mixture of any of the above (1) to (5), etc. Examples include:
[0031] Specific examples of the lactic acid include L-lactic acid, D-lactic acid, DL-lactic acid, or cyclic dimers thereof such as L-lactide, D-lactide, DL-lactide, or a mixture thereof.
[0032] Examples of the aliphatic polycarboxylic acid constituting the copolymer include oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, undecanedioic acid, and dodecanedioic acid. The aliphatic polycarboxylic acid may be an anhydride.
[0033] Examples of the aliphatic polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentyl glycol, tetramethylene glycol, and 1,4-cyclohexanedimethanol.
[0034] Examples of the aliphatic hydroxycarboxylic acid other than lactic acid that constitutes the copolymer include glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, and 6-hydroxycaproic acid.
[0035] The polylactic acid resin contained in the resin composition may be only a crystalline polylactic acid resin, or may contain a crystalline polylactic acid resin and an amorphous polylactic acid resin.
[0036] The polylactic acid resin contained in the resin composition preferably contains a copolymer in which D-form (D-lactic acid) and L-form (L-lactic acid) of lactic acid are copolymerized. The ratio of D-form in the copolymer is preferably 0.1 mol% or more and 3 mol% or less. The polylactic acid resin containing the copolymer preferably has a melting point of 160°C or more and 180°C or less. Such a polylactic acid resin has advantages in terms of moldability and heat resistance.
[0037] The D-form ratio in the copolymer may be calculated from the ratio of D-form to L-form contained in the lactic acid, which is the raw material used to produce the copolymer. The D-form ratio can also be calculated from the chromatogram obtained by measuring the copolymer by liquid chromatography after pyrolysis. For example, the D-form ratio can be calculated by the following method described in paragraph 0069 of Japanese Patent No. 5755097. Specifically, the copolymer is freeze-pulverized, 200 mg of the copolymer powder is fed into an Erlenmeyer flask, and 30 mL of 1N sodium hydroxide solution is added to the Erlenmeyer flask. The Erlenmeyer flask is then heated to 65°C while shaking to completely dissolve the copolymer. Then, 1N hydrochloric acid is fed into the Erlenmeyer flask to neutralize the mixture, and a decomposition solution with a pH of 4 to 7 is prepared, and a measuring flask is used to adjust the volume to a predetermined volume. Next, the decomposition solution is filtered through a 0.45 μm membrane filter, and then analyzed by liquid chromatography. The D-form ratio is calculated from the peak areas derived from the D-form and L-form based on the chart obtained. The same procedure as above is then repeated five times, and the obtained D-form ratios are each arithmetically averaged to determine the D-form ratio in the copolymer.
[0038] <Liquid chromatography measurement conditions> HPLC equipment (liquid chromatography): JASCO Corporation Product name: PU-2085 Plus type system Column: Sumitomo Analysis Center Co., Ltd. Product name: SUMICHIRAL OA5000 (4.6 mm φ × 250 mm) Column temperature: 25℃ Mobile phase: A mixture of 2 mM CuSO4 aqueous solution and 2-propanol (CuSO4 aqueous solution:2-propanol (volume ratio) = 95:5) Mobile phase flow rate: 1.0mL / min Detector: UV 254nm Injection volume: 20μL
[0039] The resin composition contains a modified polylactic acid resin, which is a modified product of polylactic acid resin, as the polylactic acid resin. The polylactic acid resin can be obtained by modifying a commercially available polylactic acid resin. In the modification, a crosslinked structure or a long chain branched structure can be provided in the molecular structure of the polylactic acid resin, or the polylactic acid resin can be made to have a high molecular weight. A chain extender such as carbodiimide can be used to increase the molecular weight of the polylactic acid resin. In addition, the modification with a chain extender can be performed using a compound having one or more functional groups capable of undergoing a condensation reaction with a hydroxyl group or a carboxyl group present in the molecular structure of the polylactic acid resin, such as an acrylic organic compound, an epoxy organic compound, or an isocyanate organic compound. The modification can be performed by a method in which an acrylic organic compound, an epoxy organic compound, an isocyanate organic compound, or the like is bonded to the polylactic acid resin by reaction.
[0040] The modification of polylactic acid resin by crosslinking or long chain branching can be carried out, for example, by a method of reacting polylactic acid resins with each other using a radical initiator. Among the above modification methods, it is preferable to react polylactic acid resins with each other using a radical initiator, since it is possible to suppress the inclusion of other components in the polylactic acid resin foam sheet. If polylactic acid resins are reacted with each other using a radical initiator having moderate reactivity, the decomposition starting point of the polylactic acid resin in the extruder is attacked by the free radicals generated by the radical initiator, and the site becomes a crosslinking point (branching point) and can be stabilized. By such modification, the polylactic acid resin has good foamability and a high crystallization rate, so that a foam sheet and a sheet molded body having a high expansion ratio and heat resistance can be easily obtained. Examples of the radical initiator used for modifying polylactic acid resin include organic peroxides, azo compounds, and halogen molecules. Among these, organic peroxides are preferable.
[0041] Examples of the organic peroxide used in the present embodiment include peroxy esters, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxydicarbonates, peroxyketals, and ketone peroxides.
[0042] Examples of the peroxy ester include t-butylperoxy 2-ethylhexyl carbonate, t-hexylperoxy isopropyl monocarbonate, t-hexylperoxybenzoate, t-butylperoxybenzoate, t-butylperoxylaurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and t-butylperoxyisopropyl monocarbonate.
[0043] Examples of the hydroperoxide include permethane hydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide.
[0044] Examples of the dialkyl peroxide include dicumyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)-hexyne-3.
[0045] Examples of the diacyl peroxide include dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, and di(3-methylbenzoyl) peroxide.
[0046] Examples of the peroxydicarbonate include di(2-ethylhexyl) peroxydicarbonate and diisopropyl peroxydicarbonate.
[0047] Examples of the peroxyketals include 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, 1,1-di-t-butylperoxycyclohexane, 2,2-di(t-butylperoxy)-butane, n-butyl 4,4-di-(t-butylperoxy)valerate, and 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane.
[0048] Examples of the ketone peroxide include methyl ethyl ketone peroxide and acetylacetone peroxide.
[0049] In order for the foamed sheet of the present embodiment to exhibit the above-mentioned properties, it is preferable that the resin composition has a predetermined property. The modified polylactic acid resin and the resin composition containing the same will be described below.
[0050] The modified polylactic acid resin and the resin composition containing the modified polylactic acid resin in this embodiment exhibit good foamability when producing foamed products such as foamed sheets, and it is preferable that the characteristic values are adjusted to be within a certain range in order to exhibit properties such as light weight for the sheet molding. The resin composition preferably has the same characteristic values as the modified polylactic acid resin. The characteristic values of the resin composition can be measured in the same manner as the modified polylactic acid resin. The characteristic values of the resin composition and the modified polylactic acid resin can be determined by the methods described in the examples.
[0051] The modified polylactic acid resin preferably exhibits a suitable fluidity when heated in order to exhibit good foaming properties. Specifically, the melt mass flow rate (MFR) of the modified polylactic acid resin at 190°C before being used to form a foamed sheet in this embodiment can be, for example, 0.1 g / 10 min or more and 5 g / 10 min or less. The MFR may be 0.3 g / 10 min or more, or 0.5 g / 10 min or more. The MFR may be 4 g / 10 min or less, or 3 g / 10 min or less.
[0052] The modified polylactic acid resin preferably exhibits a suitable melt tension when heated in order to exhibit good foaming properties. The melt tension of the modified polylactic acid resin used in this embodiment can be, for example, 30 cN or more and 70 cN or less. The melt tension may be 35 cN or more, or 40 cN or more. The melt tension may be 65 cN or less, or 60 cN or less.
[0053] The modified polylactic acid resin preferably has a suitable melting point to exhibit good heat resistance in the sheet molding. The melting point of the modified polylactic acid resin used in this embodiment can be, for example, 160°C or more and 180°C or less. The melting point may be 165°C or more, or 168°C or more. The melting point may be 180°C or less, or 170°C or less. When multiple melting points are observed, the melting point on the highest temperature side may be the above embodiment.
[0054] The modified polylactic acid resin preferably exhibits an appropriate crystallization temperature for exhibiting good heat resistance in a sheet molding. The crystallization temperature of the modified polylactic acid resin used in this embodiment can be, for example, 80°C or higher and 100°C or lower. The crystallization temperature may be 85°C or higher, or 88°C or higher. The crystallization temperature may be 98°C or lower, or 95°C or lower. When multiple crystallization temperatures are observed, it is preferable that the crystallization temperature on the lowest side is the above-mentioned embodiment.
[0055] The modified polylactic acid resin preferably has a suitable number average molecular weight (Mn) to exhibit good foaming properties. The number average molecular weight (Mn) of the modified polylactic acid resin used in this embodiment can be, for example, 50,000 or more and 150,000 or less. The number average molecular weight (Mn) may be 60,000 or more, or 70,000 or more. The number average molecular weight (Mn) may be 140,000 or less, or 130,000 or less.
[0056] The modified polylactic acid resin preferably has a suitable mass average molecular weight (Mw) to exhibit good foaming properties. The mass average molecular weight (Mw) of the modified polylactic acid resin used in this embodiment can be, for example, 200,000 or more and 550,000 or less. The mass average molecular weight (Mw) may be 250,000 or more, or 300,000 or more. The mass average molecular weight (Mw) may be 500,000 or less, or 450,000 or less.
[0057] The modified polylactic acid resin preferably has a suitable Z-average molecular weight (Mz) to exhibit good foaming properties. The modified polylactic acid resin used in this embodiment may have a Z-average molecular weight (Mz) of, for example, 700,000 or more and 1,500,000 or less. The Z-average molecular weight (Mz) may be 800,000 or more, or 900,000 or more. The Z-average molecular weight (Mz) may be 1,400,000 or less, or 1,300,000 or less.
[0058] The modified polylactic acid resin preferably exhibits an appropriate degree of dispersion (Mw / Mn) in order to exhibit good foaming properties. The degree of dispersion (Mw / Mn) of the modified polylactic acid resin used in this embodiment can be, for example, 2.0 or more and 5.0 or less. The degree of dispersion (Mw / Mn) may be 2.5 or more, or 3.0 or more. The degree of dispersion (Mw / Mn) may be 4.5 or less, or 4.0 or less.
[0059] The modification using the organic peroxide may result in the modified polylactic acid resin being mixed with components having excessively large molecular weights that will gel when thermally melted, or may cause odor problems due to the decomposition residues of the organic peroxide.
[0060] The gel contained in the modified polylactic acid resin can cause the formation of coarse bubbles in the foamed sheet or the formation of minute protrusions called "bumps." The gel content (gel fraction) in the modified polylactic acid resin or resin composition is preferably 4% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less. The gel content (gel fraction) of the polylactic acid resin or resin composition can be determined by the following method.
[0061] <Gel content measurement method> The modified polylactic acid resin pellets are used as samples. Prepare a sample of approximately 0.5 g, and accurately weigh out the initial mass (m0(g)) of this sample. Also prepare a 200 mesh wire mesh (wire diameter φ0.05 mm) to filter the solution in which this sample is dissolved. Also accurately weigh out the initial mass (M0(g)) of this wire mesh. Place the weighed measurement sample in a 100 mL beaker. Add 50 mL of chloroform as a solvent and a stir bar to the beaker, and cover with aluminum foil. Stir with the stirrer for 2 hours and dissolve at room temperature. After 2 hours, remove the aluminum foil, and filter the dissolved material in the beaker through the 200 mesh wire mesh. After filtration, naturally dry the wire mesh in a draft for 24 hours. After drying, cool in a desiccator. After cooling, weigh the wire mesh (M1(g)) to which the resin insoluble matter is attached, and calculate the gel fraction using the following formula (2). Gel fraction (mass%) = m1(g) / m0(g) × 100 (2) m0: Initial mass of the sample (g) m1: Mass of insoluble resin (M1-M0) (g) M0: Initial mass of the wire mesh (g) M1: Total mass of insoluble resin and wire mesh (g)
[0062] The organic peroxide is preferably a peroxyester, since it can suppress the risk of gel formation and can easily modify the polylactic acid resin to a state suitable for foaming. Among peroxyesters, the organic peroxide used to modify the polylactic acid resin is preferably a peroxycarbonate-based organic peroxide such as peroxymonocarbonate or peroxydicarbonate. Among peroxycarbonate-based organic peroxides, the organic peroxide used to modify the polylactic acid resin in this embodiment is preferably a peroxymonocarbonate-based organic peroxide, and particularly preferably t-butylperoxyisopropylmonocarbonate.
[0063] The organic peroxide as described above is usually used in a ratio of 0.1 parts by mass or more to 100 parts by mass of the polylactic acid resin to be modified, although it depends on the molecular weight of the polylactic acid resin before modification. The amount of the organic peroxide added is preferably 0.2 parts by mass or more, and particularly preferably 0.3 parts by mass or more. The amount of the organic peroxide added is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and particularly preferably 1.0 parts by mass or less.
[0064] By modifying the polylactic acid resin with the organic peroxide in such a ratio, the modified polylactic acid resin can be made suitable for foaming. By adding the organic peroxide in an amount of 0.1 parts by mass or more, the effect of modification on the polylactic acid resin can be more reliably exhibited. Furthermore, by adding the organic peroxide in an amount of 2.0 parts by mass or less, the presence of gel in the modified polylactic acid resin can be suppressed.
[0065] Examples of foaming components used when forming the polylactic acid resin into an extrusion foam sheet include a foaming agent, a cell regulator, etc. That is, the resin composition contains the foaming agent and the cell regulator.
[0066] As the foaming agent, a general foaming agent can be used, and a volatile foaming agent that becomes a gas at room temperature (23°C) and normal pressure (1 atm) or a decomposition type foaming agent that generates a gas by thermal decomposition can be used. As the volatile foaming agent, for example, an inert gas, an aliphatic hydrocarbon, an alicyclic hydrocarbon, etc. can be used. As the inert gas, for example, carbon dioxide, nitrogen, etc. can be used. As the aliphatic hydrocarbon, for example, propane, normal butane, isobutane, normal pentane, isopentane, etc. can be used, and as the alicyclic hydrocarbon, for example, cyclopentane, cyclohexane, etc. can be used. In this embodiment, among the above, normal butane and isobutane can be used preferably.
[0067] The decomposition type foaming agent includes azodicarbonamide, dinitrosopentamethylenetetramine, sodium bicarbonate, or a mixture of an organic acid such as citric acid or a salt thereof and a bicarbonate.
[0068] Examples of the foam regulator include polytetrafluoroethylene, talc, aluminum hydroxide, silica, etc. The decomposition type foaming agent can adjust the foaming state by using it in combination with a volatile foaming agent, and can also be used as a foam regulator.
[0069] Various additives may be added to the resin composition constituting the polylactic acid resin foam sheet as necessary. Examples of the additives include resins other than polylactic acid resin, inorganic fillers, and various chemicals. Examples of the chemicals include crystal nucleating agents (or crystallization promoters), lubricants, antioxidants, antistatic agents, flame retardants, ultraviolet absorbers, light stabilizers, colorants, and antibacterial agents. The ratio of these additives is preferably 25 parts by mass or less, more preferably 15 parts by mass or less, per 100 parts by mass of polylactic acid resin. The ratio of these additives may be 5 parts by mass or more per 100 parts by mass of polylactic acid resin.
[0070] The resin composition preferably contains a crystallization accelerator. The crystallization accelerator is preferably a substance that functions like a plasticizer and can promote the crystallization of the polylactic acid resin. As such a crystallization accelerator, a reaction product (A) of at least one of (A1) polyol and polyol dehydration condensate, (A2) alkylene oxide mainly composed of ethylene oxide, and (A3) fatty acid having 12 to 24 carbon atoms is used.
[0071] Examples of the polyol in (A1) "polyol and polyol dehydration condensate" include glycerin, erythritol, pentaerythritol, xylitol, sorbitol, mannitol, galactitol, maltitol, etc. These are also advantageous in imparting impact resistance to the polylactic acid resin foam sheet.
[0072] The above (A2) "alkylene oxide mainly composed of ethylene oxide" indicates that the majority of the alkylene oxide is ethylene oxide, and includes those in which all of the alkylene oxide is ethylene oxide. When an alkylene oxide other than ethylene oxide is used in combination with ethylene oxide, for example, propylene oxide, butylene oxide, isobutylene oxide, etc. are used in combination.
[0073] Examples of (A3) "fatty acids having 12 to 24 carbon atoms" include saturated fatty acids such as dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), pentadecanoic acid (pentadecylic acid), hexadecanoic acid (palmitic acid), heptadecanoic acid (margaric acid), octadecanoic acid (stearic acid), icosanoic acid (arachidic acid), henicosanoic acid (henicosylic acid), docosanoic acid (behenic acid), and tetracosanoic acid (lignoceric acid); and monounsaturated fatty acids such as myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, eicosenoic acid, and erucic acid. (A3) "fatty acids having 12 to 24 carbon atoms" may be diunsaturated fatty acids such as linoleic acid, triunsaturated fatty acids such as linolenic acid, or tetraunsaturated fatty acids or pentaunsaturated fatty acids. (A3) "C12-24 fatty acid" may be a mixture of multiple fatty acids such as coconut oil fatty acid. (A3) "C12-24 fatty acid" is preferably dodecanoic acid (lauric acid), octadecanoic acid (stearic acid), etc.
[0074] In order to provide a polylactic acid resin foam sheet with excellent impact resistance, the reaction product (A) preferably has an oxyethylene group content of 20% by mass or more and 95% by mass or less. The reaction product (A) more preferably has an oxyethylene group content of 30% by mass or more and 95% by mass or less. The reaction product (A) may be either a saturated ester in which all hydroxyl groups of the polyol and the polyol dehydration condensate are esterified with a fatty acid, or a partial ester in which some of the hydroxyl groups are esterified. In order to provide a polylactic acid resin foam sheet with excellent impact resistance, the reaction product (A) preferably has a predetermined number of ester groups on average in the molecule. The average number of ester groups in the molecule of the reaction product (A) is preferably more than 2 and not more than 9, more preferably more than 2.5 and not more than 6.
[0075] As a method for producing the reaction product (A), for example, a method in which a polyol and a fatty acid are reacted under heating to esterify the polyol, and then ethylene oxide is added to the polyol in an autoclave under heating to obtain the reaction product (A) can be mentioned. In addition, a dehydration condensate of a polyol may be reacted with a fatty acid to esterify it, and then ethylene oxide may be added to the polyol and the polyol dehydration condensate in the same manner as the above method. In addition, ethylene oxide may be added to the polyol and the polyol dehydration condensate, and then the fatty acid may be reacted. In addition, there is a method in which a fatty acid ester is synthesized in advance from a fatty acid and a monohydric alcohol having a short carbon number (methanol, ethanol), and then the fatty acid is subjected to an ester exchange reaction with the polyol and the polyol dehydration condensate, and ethylene oxide is added to the polyol and the polyol dehydration condensate in the same manner as the above method to obtain the reaction product (A). The reaction product (A) thus obtained is used alone or in combination of two or more kinds in the resin composition of this embodiment.
[0076] As the crystallization promoter of this embodiment, for example, the "(B) fatty acid amide" shown below may be used instead of the above "(A) reaction product". As the crystallization promoter of this embodiment, one or more of the above (A) reaction products and one or more of the (B) fatty acid amides may be used in combination.
[0077] The (B) fatty acid amide is, for example, at least one fatty acid amide selected from the group consisting of fatty acid monoamides, fatty acid bisamides, hydroxyl-containing fatty acid monoamides, and hydroxyl-containing fatty acid bisamides, and is preferably a fatty acid amide derived from a fatty acid having 8 to 24 carbon atoms. The (B) fatty acid amide is more preferably a fatty acid bisamide such as N,N'-ethylenebisstearamide, or a hydroxyl-containing fatty acid bisamide such as N,N'-ethylenebis(12-hydroxystearamide) or N,N'-xylylenebis(12-hydroxystearamide). The fatty acid amide is effective in imparting excellent moldability to the polylactic acid resin foam sheet. The fatty acid amide is also effective in imparting excellent heat resistance and impact resistance to the sheet molded body.
[0078] In addition, examples of the crystallization accelerator that can be used include hydrocarbons such as liquid paraffin, paraffin wax, and synthetic polyethylene wax; metal soaps such as zinc stearate, calcium stearate, and magnesium stearate; ethylene glycol, diethylene glycol, and higher polyethylene glycols; propylene glycol, dipropylene glycol, and higher polypropylene glycols; 1,3-butylene glycol, 1,4-butylene glycol, and their polymers, polybutylene glycols; and polyhydric alcohols such as glycerin, diglycerin, and higher polyglycerins.
[0079] The above-mentioned crystallization accelerators, which function like plasticizers, may cause a phenomenon called "bleed-out" in which the accelerator migrates to the surface layer of the polylactic acid resin foam sheet and exudes from the surface. In particular, fatty acid amides tend to bleed out from the polylactic acid resin foam sheet during thermoforming. Although this is usually considered to be a problem, it can be advantageous in improving the uniformity of the thickness of the sheet molded body by creating a suitable slippage between the mold and the polylactic acid resin foam sheet. In other words, if good slippage is not achieved between the mold and the polylactic acid resin foam sheet, the polylactic acid resin foam sheet may be locally stretched to form thin-walled areas in the sheet molded body, but such problems can be avoided by using fatty acid amides as crystal nucleating agents. In addition, the fact that the accelerator bleeds out easily means that the amount of the accelerator remaining in the sheet molded body is reduced, and therefore, when the sheet molded body is heated in an unintended manner, it is possible to suppress the occurrence of distortion due to further crystallization.
[0080] The crystallization promoter can be used in a ratio of 0.5 parts by mass or more and 15 parts by mass or less per 100 parts by mass of polylactic acid resin. The ratio of the crystallization promoter may be 1 part by mass or more, or 1.5 parts by mass or more. The ratio of the crystallization promoter to 100 parts by mass of polylactic acid resin may be 10 parts by mass or less.
[0081] The polylactic acid resin foam sheet in this embodiment can be produced by carrying out a process of modifying polylactic acid resin using a twin-screw extruder or the like (modification process), and a process of extruding and foaming a resin composition containing the modified polylactic acid resin through an extruder equipped with a circular die at its tip (extrusion foaming process).
[0082] In the modification step, for example, a twin-screw extruder equipped with a granulation die (hot cut die) may be used to pelletize the modified polylactic acid resin immediately after the modification step. A strand die or T-die may be attached to the twin-screw extruder used in the modification step, and a step of cutting the strand or sheet and granulating the strand or sheet may be separately performed in the modification step. Also, as mentioned above, if necessary, an extrusion foaming step may be performed continuously from the modification step using a tandem extruder.
[0083] In the above-mentioned extrusion foaming process, the resin composition of this embodiment does not easily stretch, and the bubble film is unlikely to become excessively thin. That is, in the polylactic acid resin foamed sheet of this embodiment, the bubble film containing the polylactic acid resin as described above exhibits a certain level of resistance when stretched by the foaming force of the foaming agent. In addition, in the polylactic acid resin foamed sheet of this embodiment, the bubble film is likely to be thin in the center and thick in the periphery. Therefore, the polylactic acid resin foamed sheet of this embodiment exhibits excellent mechanical properties by having the thick bubble film three-dimensionally connected throughout the sheet.
[0084] The resin temperature in the extrusion foaming step is preferably higher than the melting point of the modified polylactic acid resin. The temperature difference between the resin temperature in the extrusion foaming step and the melting point of the modified polylactic acid resin is preferably 3° C. or more, more preferably 5° C. or more. When the temperature difference between the resin temperature in the extrusion foaming step and the melting point of the modified polylactic acid resin is in the above-mentioned mode, clogging of the circular die due to crystallization of the resin composition in the extrusion foaming step can be suppressed, and a foamed sheet with excellent appearance can be obtained. The temperature difference between the resin temperature in the extrusion foaming step and the melting point of the modified polylactic acid resin is preferably 20° C. or less, more preferably 15° C. or less. When the temperature difference between the resin temperature in the extrusion foaming step and the melting point of the modified polylactic acid resin is in the above-mentioned embodiment, the foamability of the resin composition in the extrusion foaming step is improved, and a foamed sheet with a high expansion ratio can be easily obtained. The resin temperature can be measured, for example, by a thermocouple installed on a breaker plate between the extruder and the circular die.
[0085] In the polylactic acid resin foam sheet of this embodiment, even if bubbles break during foaming and a hole appears in the bubble film, the bubble film surrounding the hole does not remain in its original state but shrinks and increases in thickness in a manner that is effective in exhibiting strength, so that the sheet can exhibit excellent strength even if it has a certain proportion of open bubbles.
[0086] The open cell ratio of the polylactic acid resin foam sheet is preferably 30% or less, more preferably 25% or less, and even more preferably 20% or less. The open cell ratio of the polylactic acid resin foam sheet is 30% or less, and therefore the sheet molding of the present embodiment has an advantage that the secondary foaming property in the preheating step is good and the strength of the sheet molding is high. From the viewpoint of increasing the strength of the sheet molding, the lower the open cell ratio of the polylactic acid resin foam sheet, the better, but it may be 1% or more.
[0087] The basis weight of the polylactic acid resin foam sheet is preferably 100 g / m 2 More than 800g / m 2 More preferably, it is 200 g / m or less. 2 More than 700g / m 2 The polylactic acid resin foam sheet has a basis weight of 100 g / m or less. 2 For the above reasons, the sheet molding of this embodiment has high strength, and further has the advantage that the thermoformability of the polylactic acid resin foam sheet is good, resulting in a sheet molding having a shape exactly like the molding die.
[0088] The polylactic acid resin foam sheet has a basis weight of 800 g / m 2 By satisfying the above conditions, it becomes easier for the sheet molding of this embodiment to exhibit the foam's characteristics such as light weight, heat insulation, and cushioning, and there is also the advantage that the time required for the preheating step can be shortened, thereby speeding up the molding cycle.
[0089] The thickness of the polylactic acid resin foam sheet is preferably 0.5 mm to 7 mm, more preferably 0.8 mm to 5 mm, and even more preferably 1 mm to 3 mm. When the thickness of the polylactic acid resin foam sheet is 0.5 mm or more, the sheet molded body of this embodiment has an advantage of being high in strength. When the thickness of the polylactic acid resin foam sheet is 7 mm or less, the thermoformability is good, and as a result, the sheet molded body of this embodiment has an advantage of being shaped exactly as the molded body.
[0090] <Basic weight> The basis weight of a polylactic acid resin foam sheet can be determined by cutting six pieces of 10 cm x 10 cm at equal intervals in the width direction (TD direction) of the polylactic acid resin foam sheet, excluding 20 mm at both ends, and measuring the mass (g) of each piece. The arithmetic mean of the mass (g) of each piece is calculated as 1 m. 2 The converted value is the basis weight (g / m2) of the foam sheet. 2 )
[0091] <Thickness> The thickness of the polylactic acid resin foam sheet can be determined using a dial thickness gauge SM-112 (manufactured by Techlock). The thickness is measured at 10 or more points every 5 cm in the width direction (TD direction), excluding 20 mm at both ends of the width direction (TD direction), and the arithmetic mean value of the measured values is the thickness of the polylactic acid resin foam sheet.
[0092] Next, a method for producing the sheet molded body according to this embodiment will be described. The method for producing a sheet molded body in this embodiment is a method for producing a sheet molded body by carrying out a primary step of heating the polylactic acid resin foam sheet and a secondary step of clamping the polylactic acid resin foamed sheet after the primary step between a molding die to produce a sheet molded body. In the secondary step, the polylactic acid resin foam sheet may be sandwiched between heated molds to produce a sheet molded product, and a method of further increasing the crystallinity of the sheet molded product may also be employed.
[0093] In the first step, the polylactic acid resin foam sheet can be heated by a known method such as sandwiching the polylactic acid resin foam sheet between heating plates or heating the foam sheet with an electric heater. In the method for producing a sheet molded product of this embodiment, the polylactic acid resin foam sheet is heated in the first step so that the surface temperature of the polylactic acid resin foam sheet is preferably 80° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher. The heating in the first step is preferably performed so that the surface temperature of the polylactic acid resin foam sheet is 130° C. or lower, and more preferably 120° C. or lower.
[0094] In the method for producing a sheet molded product of this embodiment, by setting the surface temperature of the polylactic acid resin foamed sheet in the first step to the above-mentioned temperature, the transferability of the molding die is improved, and the softened state of the polylactic acid resin foamed sheet is improved, so that the polylactic acid resin foamed sheet is prevented from breaking during molding. In addition, in the method for producing a sheet molded product of this embodiment, by setting the surface temperature of the polylactic acid resin foamed sheet in the first step to preferably 130°C or less, more preferably 120°C or less, the surface state of the polylactic acid resin foamed sheet is improved, and further, moderate crystallization progresses in the first step, the crystallization degree of the sheet molded product increases, and a sheet molded product with excellent heat resistance can be easily obtained.
[0095] In the second step, a pair of male and female molds is preferably used as the molding mold (metal mold). In the second step, the polylactic acid resin foamed sheet heated and softened in the first step is sandwiched between the male and female molds, shaped, and maintained in this state for a certain period of time to form a sheet molded body. In the second step, a heated male and female mold can also be used as the molding mold. In the second step, the sheet molded body can be further heated at the stage of molding, thereby increasing the crystallinity. Either the male or female mold used in the second step may be heated. From the viewpoint of uniformly heating the entire polylactic acid resin foamed sheet, it is preferable that both the male and female molds used in the second step are uniformly heated. By uniformly heating the entire polylactic acid resin foamed sheet, the crystallinity can be increased evenly throughout the entire sheet molded body.
[0096] The secondary step is carried out by adjusting the temperature of the mold (metal mold) to preferably 100° C. or less, more preferably 90° C. or less, and even more preferably 50° C. or less. The secondary step has the advantage that the surface condition of the sheet molded body is improved by adjusting the heated mold to 100° C. or less. The secondary step may usually be carried out by adjusting the temperature of the mold to room temperature (25° C.) or higher. That is, by using the polylactic acid resin foam sheet of the present embodiment, a sheet molding having excellent heat resistance can be produced without carrying out a heat setting (heat treatment) step.
[0097] The surface temperature of the polylactic acid resin foam sheet in the first process can be measured by a laser radiation thermometer or the like when the polylactic acid resin foam sheet is heated by radiant heat, hot air, or the like. When the polylactic acid resin foam sheet is heated by heat transfer by contacting a heated belt or hot plate, the surface temperature of the belt or hot plate can be taken as the surface temperature of the polylactic acid resin foam sheet. The surface temperature of the belt or hot plate can be directly measured by contacting the probe of a contact thermometer. The temperature of the mold in the second process can also be measured by contacting the probe of a contact thermometer to the surface of the mold.
[0098] In the method for producing a sheet molded body of this embodiment, it is preferable that the first step and the second step are performed consecutively. That is, in an apparatus for producing a sheet molded body, it is preferable that a heating furnace for performing preheating in the first step and a molding die (metal mold) for performing the molding step in the second step are provided side by side. By producing a sheet molded body in the above-mentioned manner, the second step can be performed without excessive crystallization of the polylactic acid resin foamed sheet preheated in the first step, and good moldability of the polylactic acid resin foamed sheet in the second step can be ensured, and at the same time, since the crystallization continues to progress during the second step, it is possible to produce a sheet molded body having a sufficient degree of crystallization to exhibit heat resistance.
[0099] In the process of transition from the first step to the second step, the surface temperature of the polylactic acid resin foam sheet heated in the first step is preferably maintained. Specifically, in the process of transition from the first step to the second step, the surface temperature of the polylactic acid resin foam sheet is preferably 80° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher. In the second step, the surface temperature of the polylactic acid resin foam sheet is preferably 130° C. or lower. This allows the progress of crystallization of the polylactic acid resin foam sheet started in the first step to continue in the second step, making it possible to produce a sheet molded product having a sufficient degree of crystallinity to exhibit heat resistance.
[0100] In the first step, the time for heating the polylactic acid resin foam sheet (preheating time (t1)) is preferably from 5 to 15 seconds, more preferably from 7 to 13 seconds.
[0101] In the secondary step, the time for which the polylactic acid resin foam sheet is sandwiched between the molds and held (mold holding time (t2)) is preferably 25 seconds or less, more preferably 20 seconds or less, and more preferably 15 seconds or less. The shorter the mold holding time (t2), the better, but it may be 5 seconds or more.
[0102] The time required to transition from the first step to the second step (transition time) is preferably 10 seconds or less, more preferably 7 seconds or less, and even more preferably 5 seconds or less. The shorter the transition time, the more preferable, but it may be 1 second or more. When the transition time is within the above range, the polylactic acid resin foam sheet heated in the first step can be transferred to the second step without an excessive decrease in surface temperature. This makes it possible to ensure good moldability of the polylactic acid resin foam sheet in the second step and excellent heat resistance of the produced molded sheet.
[0103] The sheet molded body produced by the method for producing a sheet molded body of the present embodiment has a crystallinity of 20% or more, and is therefore excellent in heat resistance. The crystallinity of the sheet molded body is preferably 25% or more, and more preferably 30% or more. The crystallinity that the sheet molded body can achieve is usually 60% or less.
[0104] The sheet molded article of the present embodiment has excellent heat resistance and can therefore be suitably used as food packaging containers such as lunch boxes, instant noodle containers, and microwaveable containers.
[0105] The above examples of the polylactic acid resin foam sheet and sheet molded body of this embodiment, and the manufacturing methods thereof, are merely restrictive examples, and the present invention is in no way limited to the above examples, and can be implemented by making appropriate modifications to the above examples. As described above, the present embodiment includes the following disclosure.
[0106] (1) A polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The temperature at which the relative crystallinity reaches 50% (T h ) is 115°C or less.
[0107] (2) The crystallization onset temperature (T s ) is 80° C. or less.
[0108] (3) The crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h ) is 35°C or less.
[0109] (4) The polylactic acid resin foam sheet according to any one of (1) to (3), wherein the calorific value (b2) at the cold crystallization peak is 25 J / g or more.
[0110] (5) The polylactic acid resin foam sheet according to any one of (1) to (4), wherein the polylactic acid resin composition contains the polylactic acid resin, which is a copolymer in which D- and L-forms of lactic acid are copolymerized, the content of the D-form in the copolymer is 0.1 to 3 mol %, and the melting point of the copolymer is 160 to 180°C.
[0111] (6) The polylactic acid resin foam sheet according to any one of (1) to (5), wherein the polylactic acid resin composition contains, as the polylactic acid resin, a modified polylactic acid resin which is a product modified with an organic peroxide.
[0112] (7) The polylactic acid resin foam sheet according to any one of (1) to (6), wherein the polylactic acid resin foam sheet has a crystallinity of 10% or more.
[0113] (8) The polylactic acid resin foam sheet according to any one of (1) to (7), wherein the polylactic acid resin composition contains a crystallization promoter.
[0114] (9) A thermoformed product of the polylactic acid resin foam sheet according to any one of (1) to (8), which has a crystallinity of 20% or more.
[0115] (10) The sheet molded article according to (9), which is a food packaging container.
[0116] (11) A method for producing a sheet molded body by thermoforming a resin foam sheet, comprising the steps of: The resin foam sheet is a polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The polylactic acid resin foam sheet is A polylactic acid resin foam sheet having a temperature of 115°C or less when a relative crystallinity of 50% is reached in a cold crystallization peak observed during a temperature rise process at a heating rate of 50°C / min in a heat flux differential scanning calorimetry, a first step of heating the polylactic acid resin foam sheet; and a second step of sandwiching the polylactic acid resin foam sheet subjected to the first step between a mold to produce a sheet molded body.
[0117] (12) In the first step, The method for producing a sheet molded product according to (11), wherein the polylactic acid resin foam sheet is heated so that the surface temperature of the sheet becomes 80 to 130°C.
[0118] (13) In the second step, The method for producing a sheet molded body according to (11) or (12), wherein the temperature of the mold is 100° C. or lower. EXAMPLES
[0119] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these. isn't it. (Reference production example 1) <Preparation of modified polylactic acid resin> A mixture was obtained by stirring and mixing 100 parts by mass of the polylactic acid resin (A) and 0.6 parts by mass of an organic peroxide in a ribbon blender. The resulting mixture was fed into a twin-screw extruder with a diameter of 57 mm (L / D=31.5). The mixture was melt-kneaded in a twin-screw extruder with the feed section set at 140°C and the subsequent temperatures set at 200°C and the rotation speed set at 120 rpm, and the kneaded material was extruded in the form of strands at an output rate of 50 kg / h from a die with a 3 mm diameter and 18 holes attached to the tip of the extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30° C. to cool it. The cooled strands were cut with a pelletizer to obtain pellets of the modified polylactic acid resin.
[0120] (Reference production examples 2-4) For Reference Manufacturing Examples 2 to 4, modified polylactic acid resins were prepared in the same manner as Reference Manufacturing Example 1, except that the type of polylactic acid resin and the amount of organic peroxide added (amount added (parts by mass) per 100 parts by mass of polylactic acid resin) were changed. Table 1 shows the polylactic acid resins used in Reference Production Examples 1 to 4, and the amounts (parts by mass) of organic peroxides added per 100 parts by mass of polylactic acid resin. The types of polylactic acid resins (A to D) and the organic peroxides shown in Table 1 are detailed below. Polylactic acid resin (A): Nature Works, product name: Biopolymer Ingeo 3100HP (MFR = 12.6 g / 10 min, D-form ratio = 0.4 mol%, melting point = 176.7°C) Polylactic acid resin (B): Manufactured by Anhui Fengyuan Futairaiju Lactic Acid Co., Ltd., product name "FY601" (MFR=12.9g / 10min, D-form ratio=0.6mol%, melting point=172.7℃) Polylactic acid resin (C): Nature Works, product name: Biopolymer Ingeo 6202D (MFR = 10.1 g / 10 min, D-isomer ratio = 1.4 mol%, melting point = 164.8°C) Polylactic acid resin (D): Manufactured by Anhui Fengyuan Futairaiju Lactic Acid Co., Ltd., product name: "FY804" (MFR = 7.3g / 10min, D-form ratio = 3.5mol%, melting point = 149.8℃) Organic peroxide: Manufactured by Nouryon Chemical Industries, product name "Trigonox BPIC-C75" (t-butylperoxyisopropyl monocarbonate, 1-minute half-life temperature = 158.8°C)
[0121] The melt mass flow rate (MFR), melt tension, gel fraction, melting point, crystallization temperature, number average molecular weight (Mn), mass average molecular weight (Mw), Z-average molecular weight (Mz), and dispersity (Mw / Mn) of the modified polylactic acid resin of each reference production example were measured. The gel fraction was measured by the method described above. The other items were measured by the following methods.
[0122] <Melt Mass Flow Rate (MFR)> The melt mass flow rate (MFR) of polylactic acid resin and modified polylactic acid resin was measured using a "Semi-Auto Melt Indexer 2A" manufactured by Toyo Seiki Seisakusho Co., Ltd. The MFR was measured under the following conditions in accordance with the method for measuring the time it takes for a piston to move a specified distance described in JIS K7210-1:2014 "Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1" Method B. The samples for measurement were vacuum dried at 90°C for at least 4 hours, and after drying, they were vacuum packed in nylon polybags for vacuum packing and stored in a desiccator until immediately before measurement.
[0123] (Measurement conditions) Sample: 3-8g Preheat time: 200 seconds Load Hold: 30 seconds Test temperature: 190℃ Test load: 21.18N Piston travel distance (interval): 4mm Number of tests: 3 The arithmetic mean of the measured values obtained in each test was taken as the MFR (g / 10 min).
[0124] <Melt tension> The melt tension of the modified polylactic acid resin was measured using a capillary rheometer "Capillograph 1D" (special specification for heating furnace) manufactured by Toyo Seiki Seisakusho Co., Ltd. and "Rheotens 71.97" manufactured by Goettfert. The melt tension of the modified polylactic acid resin was measured under the following conditions. The samples were vacuum-dried at 90°C for at least 4 hours in advance, and after drying, they were placed in nylon plastic bags for vacuum packing, vacuum-packed, and stored in a desiccator until immediately before measurement. Rheotens 71.97 was installed so that the distance from the die exit of the Capillograph 1D to the measurement part was 80 mm. (Note that in cases where Rheotens could not be brought close enough to 80 mm due to interference, measures were taken to avoid interference and Rheotens was set in the designated location.) First, the sample was filled into a barrel heated to a test temperature of 190° C. and then preheated for 5 minutes. The measurement time was not to exceed 10 minutes, including the preheating time, from the time the barrel was filled. Next, a piston was inserted from the top of the barrel and the molten resin was extruded into a string-like shape. At this time, the piston descending speed (20 mm / min) was kept constant and the extruded string-like material was passed through a Rheotens wheel. Thereafter, the take-up speed was gradually increased and the melt tension of the sample was measured. Regarding the measurement results, the average of the maximum and minimum tension values just before the point at which the string-like material broke was taken as the melt tension of the sample. If there was only one maximum point on the tension chart, that maximum value was taken as the melt tension. If the string-like material became thinner and the winding became idling, that point was taken as the break point, and the average of the maximum and minimum tension values just before that point was taken as the melt tension of the sample.
[0125] (Measuring conditions for Capillograph 1D) Die: diameter 2.095mm, length 8mm, inlet angle 90 degrees (conical) Barrel diameter: 9.55mm Piston speed: 20mm / min Measurement temperature: 190℃
[0126] (Rheotensile measurement conditions) Wheel spacing: Top 0.7mm, bottom 1.0mm Acceleration: 10mm / s 2 Pulling speed: Initial speed 6.92mm / s
[0127] <Melting point, crystallization temperature> The melting point and crystallization temperature of the polylactic acid resin and modified polylactic acid resin were measured using a heat flux differential scanning calorimeter (heat flux DSC) as follows. The measurements were performed according to the methods described in JIS K7122:1987, JIS K7122:2012 "Methods for measuring heat of transition of plastics" and JIS K7121:1987, 2012 "Methods for measuring transition temperature of plastics." The sampling method and heating rate conditions were as follows: 5.5±0.5 mg of the sample was packed into an aluminum measurement container (Hitachi High-Tech Science Corporation, product code: GAA-0065) so that there were no gaps at the bottom, and then an aluminum lid (Hitachi High-Tech Science Corporation, product code: GAA-0064) was placed on the container. Next, a differential scanning calorimeter (Hitachi High-Tech Science Corporation, "NEXTA DSC600") was used to heat and cool the sample in the following steps under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) The temperature was raised from 30° C. to 210° C. (first temperature raising process), and then held for 10 minutes. (Step 2) The sample was quickly removed from the measurement device, allowed to stand at room temperature for 10 minutes, and then returned to the measurement device at 30°C. (Step 3) The temperature was increased from 30°C to 210°C (second temperature increase process). All heating rates were 5°C / min. Alumina was used as the reference material.
[0128] (Melting Point) Using the analysis software attached to the apparatus, the temperature at the top of the endothermic peak observed during the second heating process was read and taken as the melting temperature (melting point). (crystallization temperature) Using the analysis software attached to the apparatus, the top temperature of the exothermic peak observed during the second heating process was read and determined as the crystallization temperature.
[0129] <Number average molecular weight (Mn), mass average molecular weight (Mw), Z average molecular weight (Mz) and dispersity (Mw / Mn)> The number average molecular weight (Mn), mass average molecular weight (Mw), Z average molecular weight (Mz) and dispersity (Mw / Mn) of the modified polylactic acid resin and the foam sheet were measured by gel permeation chromatography (GPC). 20 mg of the sample was taken, and then 6 mL of chloroform was added thereto and gently shaken manually, and the sample was filtered through a non-aqueous 0.45 μm chromatodisk manufactured by GL Sciences Inc. or a non-aqueous 0.45 μm syringe filter manufactured by Shimadzu GLC Corp. to prepare a measurement sample. The measurement sample was measured by a chromatograph under the following measurement conditions, and the number average molecular weight (Mn), mass average molecular weight (Mw), Z-average molecular weight (Mz) and dispersity (Mw / Mn) of the sample were obtained from a standard polystyrene calibration curve prepared in advance.
[0130] [Equipment used] Tosoh Corporation "HLC-8320GPC EcoSEC" Gel Permeation Chromatograph (with built-in RI and UV detectors) [GPC measurement conditions] Sample side Guard column = TSK guardcolumn HXL-H (6.0mm x 4.0cm) x 1, manufactured by Tosoh Corporation Measurement column: Tosoh Corporation's TSKgel GMHXL (7.8 mm I.D. x 30 cm) x 2 in series Reference side: Resistance tube (inner diameter 0.1 mm x 2 m) x 2 in series Column temperature = 40 °C Mobile phase = chloroform Mobile phase flow rate: Reference pump = 0.5mL / min Sample pump: 1.0 mL / min Detector = RI detector Injection volume = 50μL Measurement time = 25 min Sampling pitch = 500 msec
[0131] The standard polystyrene samples used for the calibration curve were "STANDARD SM-105" and "STANDARD SH-75" manufactured by Showa Denko K.K., with mass average molecular weights of 5,620,000, 3,120,000, 1,250,000, 442,000, 151,000, 53,500, 17,000, 7,660, 2,900, and 1,320. The above-mentioned standard polystyrene for the calibration curve was grouped into A (5,620,000, 1,250,000, 151,000, 17,000, 2,900) and B (3,120,000, 442,000, 53,500, 7,660, 1,320), and then A (2 mg, 3 mg, 4 mg, 4 mg, 4 mg) was weighed out and dissolved in 30 mL of chloroform, and B (3 mg, 4 mg, 4 mg, 4 mg, 4 mg) was also weighed out and dissolved in 30 mL of chloroform. The standard polystyrene calibration curve was obtained by injecting 50 μL of each of the prepared solutions A and B, and creating a calibration curve (cubic equation) from the retention time obtained after measurement. The number average molecular weight (Mn), mass average molecular weight (Mw), Z-average molecular weight (Mz), and dispersity (Mw / Mn) were calculated using the calibration curve. [Table 1]
[0132] Example 1 <Preparation of polylactic acid foam sheet> 100 parts by mass of the modified polylactic acid resin obtained in Reference Production Example 1 and 1.0 part by mass of a cell regulator were dry blended to prepare a mixture. The mixture was supplied through a hopper to the first extruder of a tandem extruder equipped with a first extruder (upstream) having a diameter of 50 mm and a second extruder (downstream) having a diameter of 65 mm, and was heated and melted in the first extruder. Thereafter, butane (isobutane / normal butane=35 / 65) as a foaming agent was pressure-fed into the first extruder and melt-mixed together with the above mixture. Next, this molten mixture was transferred to a second extruder with a diameter of 65 mm and uniformly cooled to a temperature suitable for extrusion foaming until the resin temperature reached 175°C. After that, the mixture was extruded and foamed through a circular die with a diameter of 70 mm at a discharge rate of 30 kg / h to obtain a cylindrical foam. The obtained cylindrical foam was placed on a 206 mm diameter mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger in diameter. It was then cut at one point on the circumference with a cutter to obtain a strip-shaped polylactic acid resin foam sheet.
[0133] <Preparation of sheet molding 1> A flat square test piece measuring 340 mm in length and 340 mm in width was cut out from the polylactic acid resin foam sheet produced in Example 1. A small single shot molding machine (manufactured by Wakisaka Engineering Co., Ltd., product name "FVS-500 type") was used, and the heater temperature of the heating furnace was set to 400°C. Next, the test piece was introduced into the heating furnace of a small single shot molding machine and preheated. The preheating time (t1) was 10 seconds, and the surface temperature of the foamed sheet after preheating was 115°C. The foamed sheet after preheating was immediately match molded using a 110°C mold (opening diameter 220 mm, bottom diameter 170 mm, height 38 mm, drawing ratio 0.17) to produce a circular dish-shaped sheet molded body (foamed container) with an opening at the top. The time the foamed sheet was held in the mold (mold holding time (t2)) was 10 seconds.
[0134] (Examples 2 to 13) A polylactic acid resin foamed sheet was produced in the same manner as in Example 1 according to the composition and extrusion conditions in Table 2. Thereafter, a sheet molded body was produced in the same manner as in Example 1 using the polylactic acid resin foamed sheet according to the molding conditions in Table 2. The details of the crystallization accelerators and cell regulators in Tables 2 to 4 are as follows. Crystallization accelerator: Trade name "TRIBIO S-920MB" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Air bubble adjuster: Matsumura Sangyo Co., Ltd., product name "Crown Talc PP"
[0135] (Comparative Examples 1 to 7) A polylactic acid resin foamed sheet was produced in the same manner as in Example 1 according to the composition and extrusion conditions in Table 3. Thereafter, a sheet molded article was produced using the polylactic acid resin foamed sheet according to the molding conditions in Table 3.
[0136] Example 14 A polylactic acid resin foamed sheet was produced in the same manner as in Example 1 according to the composition and extrusion conditions in Table 4. Thereafter, a sheet molded article was produced using the polylactic acid resin foamed sheet according to the following procedure. <Preparation of sheet molding 2> A flat square test piece measuring 340 mm long x 340 mm wide was cut out from the polylactic acid resin foam sheet. A small single shot molding machine (manufactured by Wakisaka Engineering Co., Ltd., product name "FVS-500 type") was used, and the heater temperature of the heating furnace was set to 400°C. Next, the test piece was introduced into the heating furnace of a small single shot molding machine and preheated. The preheating time (t1) was 10 seconds, and the surface temperature of the foamed sheet after preheating was 115°C. The foamed sheet after preheating was immediately match molded using a mold at 80°C (opening diameter 175 mm, bottom diameter 161 mm, height 70 mm, drawing ratio 0.40) to produce a circular bowl-shaped sheet molded body (foamed container) with an opening at the top. The time during which the foamed sheet was held by the mold (mold holding time (t2)) was 10 seconds.
[0137] (Example 15, Comparative Examples 8 and 9) A polylactic acid resin foamed sheet was produced in the same manner as in Example 1 according to the composition and extrusion conditions in Table 4. Thereafter, a sheet molded article was produced in the same manner as in Example 14 using the polylactic acid resin foamed sheet according to the molding conditions in Table 4.
[0138] (Method of evaluating sheet molding) <Appearance of the sheet molding> The appearance of each sheet molding was visually inspected and evaluated according to the following evaluation criteria. Evaluation Criteria ⊚: The surface of the sheet molding is completely free of wrinkles or irregularities and is smooth, with a particularly beautiful appearance. ◯: The surface of the sheet molding has slight wrinkles and irregularities, but the appearance is beautiful. Δ: The surface of the sheet molding has many wrinkles and irregularities, and the appearance is poor. ×: The surface of the sheet molding has many wrinkles and irregularities, and the appearance is particularly poor.
[0139] <Productivity of sheet molding> The productivity of the sheet molding was evaluated based on the molding time (total of the preheating time (t1) and the mold retention time (t2)) of each example of the sheet molding according to the following evaluation criteria. Evaluation Criteria ◎: Molding time is 15 seconds or less. ○: The molding time is greater than 15 seconds and less than 20 seconds. △: The molding time is more than 20 seconds and less than 25 seconds. ×: Molding time is more than 25 seconds.
[0140] <Heat resistance of sheet molding (heat deformation rate)> Three circular sheet molded bodies of each example were prepared. Next, the diameter in the extrusion direction (MD1) and the diameter in the width direction (TD1) of the sheet molded body before heating were measured. Next, each test piece was placed on a flat platform in an oven without humidity control set at 100°C, heated for 150 seconds, removed from the oven, and cooled at room temperature for 30 minutes. Then, the diameters in each direction (MD2 and TD2) of the sheet molded body after heating were measured. The diameters (MD1 and MD2, TD1 and TD2) were measured using a caliper ("Digimatic Caliper" manufactured by Mitutoyo Corporation). The heat deformation rate (%) of each sheet molding was calculated by the following formula (3), and the arithmetic mean value of the three values was taken as the heat deformation rate (%) of the sheet molding and was used as the evaluation standard for heat deformation resistance. Heat deformation rate (%) = (MDr + TDr) / 2 (3) MD transformation rate (MDr) (%) = (|MD2-MD1| / MD1) × 100 TD deformation rate (TDr) (%) = (|TD2-TD1| / TD1) × 100 <Evaluation Criteria for Thermal Deformation Resistance of Sheet Molded Body> ⊚: Heat deformation rate is less than 1%. ◯: The heat deformation rate is 1% or more and less than 1.5%. △: The heat deformation rate is 1.5% or more and less than 2%. ×: Heat deformation rate is 2% or more.
[0141] <Overall evaluation of foam sheets> The foamed sheets of each example were comprehensively evaluated based on the various characteristics according to the following evaluation criteria. ◎: All items were rated as either "◎" or "〇", with two or more "◎"s. ○: All items were rated as either "◎" or "〇", with one or less being "◎". △: All items were rated as either "◎", "OK", or "△", with one or more being rated "△". ×: Any of the items was rated as “×”.
[0142] The basis weight, thickness, expansion ratio, open cell ratio, melting point, crystallinity, number average molecular weight (Mn), mass average molecular weight (Mw), Z average molecular weight (Mz), dispersity (Mw / Mn), crystallization onset temperature (T s ), the temperature at which the relative crystallinity is 50% (T h ) was measured. The melting points and crystallinity of the sheet molded bodies of the examples and comparative examples were also measured. In addition, the expansion ratio, open cell ratio, and crystallization temperature (T s ), the temperature at which the relative crystallinity is 50% (T h ) were measured by the following method. The other items were measured by the methods described above.
[0143] <Expansion ratio> Density of polylactic acid resin (1.24g / cm 3 ) and the apparent density of the foamed sheet of each example, using the following formula (4). Apparent density (g / cm 3 ) = basis weight (g / m 2 ) ÷ thickness (mm) ÷ 1000 Expansion ratio (times) = 1.24 (g / cm 3 ) ÷ apparent density (g / cm 3 ) · · · (4)
[0144] <Open cell ratio> From each foam sheet, several sheet-like samples measuring 25 mm long x 25 mm wide were cut out. The cut samples were stacked together without leaving any gaps to form test pieces with a thickness of 21 to 23 mm, and three test pieces were prepared. The test pieces were conditioned for 16 hours in a JIS K7100:1999 symbol 23 / 50, class 2 environment, and the thickness (mm) was measured. A "Digimatic Caliper" caliper made by Mitutoyo Corporation was used to measure the thickness. The thickness was measured to the nearest 1 / 100 mm, and the apparent volume (cm 3 ) was sought. Next, the volume (cm) of the test piece was measured under the following measurement conditions in the above environment using a dry automatic density meter (Shimadzu Corporation's "AccuPic II 1340-100cc").3 ) was measured. [Measurement conditions for dry-type automatic density meter] Gas used: Nitrogen Container used: 35cc Filling pressure: 0.005psig Pressure equilibrium end rate: 0.005psig / min Repeat count: 1 time The open cell ratio (%) of each test piece was calculated using the following formula (5): The arithmetic mean value of the measured open cell ratio of each test piece was taken as the open cell ratio (%) of the polylactic acid resin foam sheet of each example. Open cell rate (%) = {(apparent volume (cm 3 )-Measurement volume (cm) using a dry-type automatic density meter 3 )) / apparent volume(cm 3 )}×100···(5)
[0145] <Crystallization start temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h )> Crystallization initiation temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h The sampling method and heating rate conditions for were as follows: A sample cut from each polylactic acid resin foam sheet was packed into the bottom of an aluminum measurement container at 5.5±0.5 mg without leaving any gaps, and then the container was covered with an aluminum lid. Differential scanning calorimetry was then performed using a Hitachi High-Tech Science Corporation "NEXTA DSC600" differential scanning calorimeter. The sample was heated from 30°C to 210°C at a heating rate of 50°C / min under a nitrogen gas flow rate of 20 mL / min (first heating process), and a DSC curve was obtained. In this case, alumina was used as the reference material. Crystallization initiation temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h ) was calculated using the analysis software provided with the device. First, the crystallization onset temperature (T s ) and the calorific value (b2) were calculated. The heat generation amount (b2) was calculated based on the area (hereinafter, "cold crystallization peak area") of the cold crystallization peak (hereinafter, "exothermic peak") at the lowest temperature side observed during the first heating process at a heating rate of 50°C / min. The cold crystallization peak area was defined as the total area surrounded by the straight line connecting the start point b and the end point b of the exothermic peak in the DSC curve, and the DSC curve. The start point b was determined by reading the point where the DDSC curve leaves the low-temperature baseline in the DSC differential curve (hereinafter, "DDSC curve") in the exothermic peak, and the end point b was determined by reading the point where the DDSC curve returns to the high-temperature baseline in the DDSC curve in the exothermic peak. The starting point b at this time is defined as the crystallization onset temperature (T s ) was decided. The end point b was determined as the temperature at which the relative crystallinity became 100%. The temperature at which the relative crystallinity is 50% (T h ) was defined as the temperature at which the cumulative heat generation amount from the starting point b became 50% of the heat generation amount (b2). More specifically, the analysis software used "automatic divided integration," with the starting point b as the "integration start point" and the end point b as the "integration end point," dividing the cold crystallization peak at an integration interval of 0.2°C, and the temperature at which the relative crystallinity was 50% was defined as the temperature at which half of the total area of the cold crystallization peak was reached (relative crystallinity 50%). If there is no observation point where the relative crystallinity is exactly 50%, the temperature at the observation point where the relative crystallinity is closest to 50% is taken as the temperature at which the relative crystallinity is 50% (T h ) was adopted. At this time, the endothermic heat (a2) was also measured. The endothermic amount was calculated from the area (hereinafter, "melting peak area") of the highest temperature melting peak (hereinafter, "endothermic peak") observed during the first heating process at a heating rate of 50°C / min in Fig. 3. The melting peak area was defined as the total area surrounded by the straight line connecting the start point a and the end point a of the endothermic peak in the DSC curve, and the DSC curve. The start point a was determined by reading the point at which the DDSC curve departs from the low-temperature baseline in the endothermic peak, and the end point a was determined by reading the point at which the DDSC curve returns to the high-temperature baseline in the endothermic peak.
[0146] The results are shown in Tables 2, 3 and 4 below.
[0147] [Table 2]
[0148] [Table 3]
[0149] [Table 4]
[0150] In Examples 1 to 15 in which the present invention was applied, the sheet moldings were given an overall evaluation of "△" to "◎". On the other hand, in Comparative Examples 1 to 9, one of the evaluation items for the sheet molding was marked with "x", and the overall evaluation was marked with "x".
[0151] From the above, it can be seen that the present invention can provide a polylactic acid resin foam sheet that makes it possible to shorten the time required for the molding process of the polylactic acid resin foam sheet in order to obtain a sheet molding having excellent heat resistance. [Explanation of symbols]
[0152] 1: Polylactic acid resin foam sheet, 100: Sheet manufacturing equipment
Claims
1. A polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The temperature at which the relative crystallinity becomes 50% (T h ) is 115°C or less.
2. The crystallization onset temperature (T s 2. The polylactic acid resin foam sheet according to claim 1, wherein the temperature of the foam is 80° C. or lower.
3. The crystallization onset temperature (T s ) and the temperature at which the relative crystallinity is 50% (T h 3. The polylactic acid resin foam sheet according to claim 1, wherein the difference (ΔT) between the temperature of the foam and the temperature of the innermost layer is 35° C. or less.
4. 3. The polylactic acid resin foam sheet according to claim 1, wherein the heat release amount (b2) at the cold crystallization peak is 25 J / g or more.
5. 3. The polylactic acid resin foam sheet according to claim 1 or 2, wherein the polylactic acid resin composition contains the polylactic acid resin which is a copolymer in which D- and L-forms of lactic acid are copolymerized, the content of the D-form in the copolymer is 0.1 to 3 mol %, and the melting point of the copolymer is 160 to 180° C.
6. 3. The polylactic acid resin foam sheet according to claim 1, wherein the polylactic acid resin composition contains, as the polylactic acid resin, a modified polylactic acid resin which is a product modified with an organic peroxide.
7. 3. The polylactic acid resin foam sheet according to claim 1, having a crystallinity of 10% or more.
8. 3. The polylactic acid resin foam sheet according to claim 1, wherein the polylactic acid resin composition contains a crystallization promoter.
9. 3. A thermoformed product of the polylactic acid resin foam sheet according to claim 1 or 2, having a crystallinity of 20% or more.
10. The sheet molded article according to claim 9, which is a food packaging container.
11. A method for producing a sheet molded body by thermoforming a resin foam sheet, comprising the steps of: The resin foam sheet is a polylactic acid resin foam sheet composed of a polylactic acid resin composition containing a polylactic acid resin, The polylactic acid resin foam sheet is A polylactic acid resin foam sheet, the temperature at which a relative crystallinity of 50% is reached in a cold crystallization peak observed during a temperature rise process at a heating rate of 50° C. / min in a heat flux differential scanning calorimetry measurement is 115° C. or lower, a first step of heating the polylactic acid resin foam sheet; and a second step of sandwiching the polylactic acid resin foam sheet subjected to the first step between a mold to produce a sheet molded body.
12. In the first step, The method for producing a sheet molded product according to claim 11, wherein the polylactic acid resin foam sheet is heated so that the surface temperature of the sheet becomes 80 to 130°C.
13. In the second step, The method for producing a sheet molded body according to claim 11 or 12, wherein the temperature of the mold is set to 100° C. or lower.
Citation Information
Patent Citations
Method for manufacturing polylactic acid resin foamed article and polylactic acid resin foam sheet for thermoforming
JP2005145058A